Electronic Shooting Simulator Family "STrIzh": Implementation Levels and Free Software Structure - S. F. Egorov (Приборы и методы измерений)
Development of rifle electronic simulators (i.e. for hand weapons and not using ammunition) is an important task, since the production of any type of small arms according to regulatory documents also requires the production of a simulator to instill aiming and firing skills. A family of electronic shooting simulators "STrIzh" of four levels of implementation: initial, basic, professional and special is described. Structural diagrams of different configurations are given, functional purpose and capabilities of each level of simulators are shown. The initial level allows independent assemble the simulator from publicly available elements (laptop, webcam, weapon layouts, IR LEDs), which can contribute to widespread use both in schools and at home, but is low in accuracy and manufacturabili (requires daily calibration). The basic level also allows independent assemble the simulator, and less publicly available elements (laptop, projector, mockup weapons, laser emitters, FHD camera), which allows to be used both in schools and in DOSAAF structures, and has acceptable accuracy and manufacturability (a weekly calibration is enough, but assembling a mock-up weapon with laser emitters requires adjustments). It is recommended to limit the special level to virtual reality simulators, including a helmet with a smartphone and a mockup of a weapon with its smartphone which also contributes to its public availability and widespread use. The simulator software algorithm should fully support all implementation levels with different configurations and include a multimedia shooting training system. Mathematical models of external ballistics of thrown equipment for Kalashnikov assault rifle, Makarov pistol, hand-held anti-tank grenade launcher 7 products are described in detail, taking into account changes in atmospheric factors (temperature, air pressure, wind force) and dispersion of various types of ammunition. The above review of rifle simulators and their experience revealed the main trends of improvement – use of virtual reality and training not only direct shooting skills, but also training in the eligibility of the use of weapons, safe handling of them and even tactical interaction in the group.